Antimicrobial Potential of Curcumin: Therapeutic Potential and Challenges to Clinical Applications - Yaseen Hussain; Waqas Alam; Hammad Ullah; Marco Dacrema; Maria Daglia; Haroon Khan; Carla Renata Arciola (MDPI AG, 2022)
Curcumin is a bioactive compound that is extracted from Curcuma longa and that is known for its antimicrobial properties. Curcuminoids are the main constituents of curcumin that exhibit antioxidant properties. It has a broad spectrum of antibacterial actions against a wide range of bacteria, even those resistant to antibiotics. Curcumin has been shown to be effective against the microorganisms that are responsible for surgical infections and implant-related bone infections, primarily Staphylococcus aureus and Escherichia coli. The efficacy of curcumin against Helicobacter pylori and Mycobacterium tuberculosis, alone or in combination with other classic antibiotics, is one of its most promising antibacterial effects. Curcumin is known to have antifungal action against numerous fungi that are responsible for a variety of infections, including dermatophytosis. Candidemia and candidiasis caused by Candida species have also been reported to be treated using curcumin. Life-threatening diseases and infections caused by viruses can be counteracted by curcumin, recognizing its antiviral potential. In combination therapy with other phytochemicals, curcumin shows synergistic effects, and this approach appears to be suitable for the eradication of antibiotic-resistant microbes and promising for achieving co-loaded antimicrobial pro-regenerative coatings for orthopedic implant biomaterials. Poor water solubility, low bioavailability, and rapid degradation are the main disadvantages of curcumin. The use of nanotechnologies for the delivery of curcumin could increase the prospects for its clinical application, mainly in orthopedics and other surgical scenarios. Curcumin-loaded nanoparticles revealed antimicrobial properties against S. aureus in periprosthetic joint infections.